Microwave and millimeter-wave electronic packaging - Sturdivant, Rick (Artech House, 2014)
This resource presents you with the electronic packaging issues unique to microwave and millimeter-wave frequencies and reviews lower frequency packaging techniques so they can be adapted to higher frequency designs.